Prespektif Perempuan Non Muslim Suku Batak terhadap Poligami: (Studi Kasus di Kota Medan) - Aurelleya Theransq; Sundari; Said Rizal (Jurnal Hukum Lex Generalis, 2025)
The purpose of this study is to analyze and explain the practice of polygamy in Indonesia. Analyze polygamy, according to the views of non-Muslim women, especially in the Batak tribe. Examine how polygamy began. The research methodology used in this study is qualitative. Based on the results of the study and discussion of the practice of polygamy in Medan City from the perspective of non-Muslim Batak women, it can be concluded that polygamy is still a complex and controversial phenomenon in society. Polygamy can have significant emotional, financial, and social impacts on the women involved.